Genotyping-by-sequencing uncovers a Thinopyrum 4StS·1JvsS Robertsonian translocation linked to multiple stress tolerances in bread wheat - Kruppa, Klaudia; Türkösi, Edina; Holušová, Kateřina; Kalapos, Balázs; Szakács, Éva; Cséplő, Mónika; Farkas, András; Ivanizs, László; Szőke-Pázsi, Kitti; Mikó, Péter; Kovács, Péter; Gulyás, Andrea; et al. (TAG. Theoretical and applied genetics. Theoretische und angewandte Genetik, 2024)
GBS read coverage analysis identified a Robertsonian chromosome from two Thinopyrum subgenomes in wheat, conferring leaf and stripe rust resistance, drought tolerance, and maintaining yield stability. Agropyron glael (GLAEL), a Thinopyrum intermedium × Th. ponticum hybrid, serves as a valuable genetic resource for wheat improvement. Despite its potential, limited knowledge of its chromosome structure and homoeologous relationships with hexaploid wheat (Triticum aestivum) has restricted the full exploitation of GLAEL's genetic diversity in breeding programs. Here, we present the development of a 44-chromosome wheat/GLAEL addition line (GLA7). Multicolor genomic in situ hybridization identified one chromosome arm from the St subgenome of Th. intermedium, while the other arm remained unclassified. Genotyping-by-sequencing (GBS) read coverage analysis revealed a unique Robertsonian translocation between two distinct Thinopyrum subgenomes, identified as 4StS·1JvsS. The GLA7 line demonstrated strong adult plant resistance to both leaf rust and stripe rust under natural and artificial infection conditions. Automated phenotyping of shoot morphological parameters together with leaf relative water content and yield components showed that the GLA7 line exhibited elevated drought tolerance compared to parental wheat genotypes. Three years of field trials showed that GLA7 exhibits similar agronomic performance and yield components to the wheat parents. This unique addition line holds promise for enhancing wheat's tolerance to multiple stresses through the introduction of new resistance genes, as well as its ability to mitigate the effects of temporary water limitation during flowering, all without negatively impacting wheat performance.
Keywords: Triticum; Plant Breeding; genotypizační techniky; fenotyp; Phenotype; Genotype; odolnost vůči nemocem; Droughts; šlechtění rostlin; pšenice; translokace genetická; chromozomy rostlin; Chromosomes, Plant; nemoci rostlin; Stress, Physiological; Agropyron; Disease Resistance; Translocation, Genetic; genotyp; Plant Diseases; fyziologický stres; Genotyping Techniques; období sucha